Optimization of Fermentation Parameters for Enhanced Bioethanol Production by Multistress-Tolerant Saccharomycodes ludwigii APRE2 Using Undetoxified Sugarcane Bagasse Hydrolysate - Preekamol Klanrit; Sudarat Thanonkeo; Warayutt Pilap; Jirawan Apiraksakorn; Khanittha Fiala; Ratanaporn Leesing; Mamoru Yamada; Pornthap Thanonkeo (Energies)
The presence of various inhibitory compounds in lignocellulosic hydrolysates poses a significant challenge for bioethanol production, requiring yeasts with exceptional multistress tolerance. This study introduces the novel application and demonstrates the robust performance of the nonconventional yeast Saccharomycodes ludwigii APRE2 for efficient bioethanol production directly from undetoxified sugarcane bagasse hydrolysate (SBH) at 37 °C. This approach critically eliminates the need for the costly detoxification pretreatments often required in industrial processes. Initial experiments confirmed S. ludwigii APRE2’s capability to ferment undetoxified SBH. To optimize fermentation efficiency, a central composite design (CCD) approach was implemented. This statistical method identified the following precise optimal parameters: sugar concentration (143.95 g/L), diammonium phosphate (4.99 g/L), pH (4.98), yeast extract (8.94 g/L), and magnesium sulfate (2.22 g/L). Under these optimized conditions, impressive results were achieved: a maximum ethanol concentration of 38.11 g/L, productivity of 1.59 g/L·h, and yield of 0.45 g/g. Notably, the ethanol productivity and theoretical yield achieved by S. ludwigii APRE2 using this inhibitor-rich, undetoxified SBH (containing acetic acid, formic acid, furfural, and 5-(hydroxymethyl)furfural) were superior to those previously reported for other ethanologenic yeasts under similar challenging conditions. This research establishes S. ludwigii APRE2 as a highly promising and industrially viable candidate for sustainable bioethanol production from lignocellulosic biomass, with its key novelty being its superior performance on undetoxified feedstocks, potentially reducing overall production costs.